Composição química e potencial antioxidante do camu-camu (Myrciaria dubia) e sua influência em composições nutricionais utilizadas na piscicultura - Pereira, Evelyn Diane (2019)
Studies involving natural antioxidant compounds have drawn the attention of the scientific community, as natural antioxidants are associated with beneficial effects on human and animal health. In this study the potential of the fruit (camu-camu), as well as of different diets for alternative feeding of fish, were evaluated, based on analyzes of the centesimal composition and methodologies to determine the antioxidant potential. In addition, analytical methodologies were developed for the identification and quantification of flavonoids, phenolic acids and ascorbic acid, and also the validation of the ascorbic acid quantification methodology.The antioxidant potential was evaluated from four existing methodologies, ABTS free radical inhibition, chelating ability, determination of total phenolic compounds and total flavonoids. In order to quantify the flavonoids and phenolic acids, an analytical methodology by high performance liquid chromatography (HPLC) was developed, since the already described were not applied to the matrix of interest. It is worth noting that camu-camu fruit are attributed to several properties, one of the main ones being the high ascorbic acid content, however, there is a lack of applicability of the existing methodologies for its quantification. In this study, a methodology was developed and validated using HPLC. After the analysis and evaluation of the data, the antioxidant potential of camu-camu was verified and it was concluded that this fruit has antioxidant potential as a pulp and fruit in natura, as well as when used as nutritional enrichment in different nutritional compositions, which transfers its radical inhibition properties, as it has, among others, a high percentage of ascorbic acid (on average 0.0028 g of ascorbic acid per g of sample). This transfer can be verified through the analyzes performed also using the reference composition (without addition of the fruit).